Rediscovery of the Endangered Pseudophilotes fatma (Oberthür, 1890) (Lepidoptera: Lycaenidae) in Algeria after 71 years, with an update on its distribution and designation of a lectotype - Bouam, Idriss; Tennent, W. John; Abdennebi, Ahmed; Benmokhtar, Elalmi (Zootaxa, 2024)
Pseudophilotes fatma (Oberthür, 1890) is a Palearctic butterfly species endemic to the Maghreb region, characterised by a highly restricted distribution and “Endangered” conservation status. Recent field observations in Batna Province, northeastern Algeria, have documented new localities for P. fatma, marking its rediscovery after a 71-year absence. We updated the global distribution map for this species and highlight the urgent need for conservation actions to ensure its persistence. A lectotype is designated for Lycæna bavius var. fatma Oberthür, 1890.